POLAND’S “FAMILY 500+” PROGRAM AS AN OPPORTUNITY TO SOLVE THE PROBLEMS OF FAMILY AND DEMOGRAPHIC POLICY - Anna Milewska; Daniel Błażejczyk (Polityki Europejskie, Finanse i Marketing)
The goal of this article was to identify and characterize the socio-economic effects of the introduction of the “Family 500+” program in Poland. The research part focused on checking the implementation of the assumptions, which were placed on the introduction of the "Family 500+" program. The main focus of the study was fertility, the improvement of which is a key goal of the program. The research methods used in the article were: data analysis method - data on the number of births of children in Poland, the fertility rate as well as the method of synthesis, inference and interpretation were analyzed. On the basis of the data analysis, conclusions were drawn and their nature explained. This was done in order to reflect on the effectiveness of public spending on the "Family 500+" program. To achieve the intended objective, research and analysis were carried out using selected indicators and statistical data. Their results allowed to verify the effectiveness of public funds spent on the indicated program.